APLICACIÓN DE PROCEDIMIENTOS DEL FABRICANTE EN LA REPARACIÓN DEL SISTEMA DE INYECCIÓN ELECTRÓNICA - VILLALTA ROMERO, LUIS ALBERTO (2015)
The present Project is based on acquired knows in PROTMEC classrooms, its target is the installation of the Electronic Fuel Injection. For this reason , it´s pick the Jeep Grand Cherokee model 1996, for the Fuel Injection System reconstruction, type MPFI; this system has several components that are used on actually vehicles, even had consideration the manufacturer´s car and rebuild information. Some systems components were fixed and others were installed that they´re not on the car. Then check the correct function of the Fuel System with the use of electronic diagnosis tool and the use of electrical diagrams that indicated the specific characteristics of each component and function. This project brings a help to the Tecnologia Mecanica Automotriz´s students to learn best the function of Electronic Fuel Injection System.